Assessment of Chemical Effects on Wellbore Stability in Transition Shale Formation. (20th April 2022) - Lin, Hai; Deng, Jingen; Luo, Chao; Li, Lin; Liu, Hailong
Abstract : Substantial research has been conducted on the mechanisms responsible for the wellbore collapse in shale formations. For chemically active soft shale formations, pore pressure and stress change due to osmotic pressure and hydration swelling are usually recognized as the primary mechanisms, while for chemically inactive hard shale formation, wellbore instability is generally attributed to weak structural planes like bedding planes and microcracks. In this paper, experimental testing and analytical and numerical analyses are performed to reveal the dominant mechanism of the frequently encountered severe wellbore instability events in the middle-deep shale formation in the Bohai oil field of China. It is evidenced from the physical and chemical experimental testing that the middle-deep shale features both medium chemical activity and abundant bedding planes and microcracks, indicating that the middle-deep shale is in the transition process from chemically actively soft shale to the chemically inactive but laminated and fractured hard shale. Mechanical testing also shows considerable strength degradation of the middle-deep transition shale due to drilling fluid-shale interaction. Analysis through a hydro-chemo-mechanical coupling theory shows that the extent of the damage zone around the wellbore is limited if only pore pressure change and hydration swelling caused by the chemical difference between the drilling fluid and the formation fluid are considered, which cannot explain the severe wellbore collapse in the drilling process. In contrast, when pore pressure increase and strength degradation of the shale due to drilling fluid penetration along the bedding planes and microcracks are taken into account, a damage zone of 3 4 times of the wellbore diameter can be generated, implying that the dominant mechanism of the wellbore instability in the middle-deep transition shale formation should be the pore pressure change and strength degradation resulted from drilling fluid penetration along the bedding planes and microcracks.